Analisis Zakat Sebagai Instrumen Redistribusi Kekayaan Untuk Mengurangi Kesenjangan Sosial - Siti; Nurhayati; Mili Haryanti (LPPM STAI DARUSSALAM LAMPUNG, 2024)
Zakat is one of the important instruments in Islamic teachings with the aim of achieving social justice. Where in the context of wealth redistribution, zakat plays an important role as a mechanism in reducing social inequality through the distribution of wealth from the capable community group (musakki) to the needy group (mustahik). This study aims to analyze how the role of zakat can function as an instrument of wealth redistribution to reduce social inequality in society. This study uses a qualitative approach with a literature study method in exploring the concept and implementation of zakat in the socio-economic context.